(untitled) (Third Sector Social Economic Review, 2023)
With this research, it is aimed to determine the elements of corporate social responsibility that affect competitive advantage in accommodation businesses. Within the scope of the research, data were collected from middle and senior managers working in accommodation businesses operating in Sapanca and Maşukiye regions. When the numerical data provided as a result of regression and correlation analyses are analyzed; positive relationships were determined between competitive advantage and corporate social responsibility dimensions, and while the significant effect of legal responsibility and ethical responsibility among the dimensions that constitute corporate social responsibility on the explanation of competitive advantage could not be determined, the significant positive effect of economic responsibility and voluntary responsibility was determined at a high level. According to the results of the study, it is recommended that hotel businesses should communicate initiatives that prioritize social interests to all stakeholders, especially employees, by using organizational communication tools and raise awareness on this issue.